2020
DOI: 10.5114/pedm.2020.95627
|View full text |Cite
|
Sign up to set email alerts
|

Low serum copper and zinc concentrations in North Indian children with overweight and obesit

Abstract: Introduction: There are limited data on the alterations of serum copper and zinc, which have been proposed to have associations among children with obesity. Material and methods: A total of 173 children were enrolled and grouped into overweight/obese (n = 69) and non-obese (n = 104) according to CDC 2000 growth charts. Serum and whole blood zinc and copper concentrations were measured by validated ICP-MS method, and copper/zinc ratios were calculated and correlated to various anthropometric parameters. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Agilent 7700x ICP-MS with collision cell technology will be used, which operates on Helium (He) collision mode, to remove all polyatomic interferences using a single set of conditions, giving lower levels of interference and better long-term stability. Whole blood and serum samples (200 µl) will be taken, followed by the addition of 2 mL of nitric acid, 0.5 ml of hydrogen peroxide, and 10 µl of gold solution (10 µg/l) in a microwave digestion tube [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Agilent 7700x ICP-MS with collision cell technology will be used, which operates on Helium (He) collision mode, to remove all polyatomic interferences using a single set of conditions, giving lower levels of interference and better long-term stability. Whole blood and serum samples (200 µl) will be taken, followed by the addition of 2 mL of nitric acid, 0.5 ml of hydrogen peroxide, and 10 µl of gold solution (10 µg/l) in a microwave digestion tube [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Vivek et al showed that zinc and copper levels are significantly lower in obesity among Indian children aged 6-16 years [63]. In a study by Perrone et al serum zinc and copper levels were lower in obese, overweight children [24].…”
Section: Obese Children May Have Inadequate Food Intake Due To Low Intake Of Vitamins a E And C But May Not Havementioning
confidence: 97%
“…seng serta tembaga ditemukan secara signifikan lebih rendah pada anak-anak dengan obesitas eksogen dibandingkan dengan kelompok kontro 10. Adapun penelitian yang dilakukan di Kabupaten Majene menunjukkan bahwa 86,4% asupan zinc pada remaja obesitas tergolong kurang dari angka kecukupan gizi Distribusi Responden Berdasarkan Jumlah Siswi Setiap Kelas XII Siswi di SMA Negeri 1 Majene Tahun 2022 Berdasarkan hasil penelitian pada tabel 1 menunjukkan bahwa dari 148 sampel, distribusi responden berdasarkan kelas yang memiliki jumlah paling banyak yaitu kelas XII MIPA 1 sebanyak 25 siswi (16,9%), kelas XII MIPA 2 sebanyak 25 siswi (16,9%) dan kelas XII MIPA 4 sebanyak 25 siswi (16,9%).…”
unclassified